Cultivating an Attitude of Honesty Through the Living Values Education Model in PAI Learning - Dewi Sinta; Syahidin Syahidin; Munawar Rahmat; Saepul Anwar; Walid In'am Ahmad; Abid Nurhuda; Muhammad Faqihudin Ismail (PT. Student RIhlah Indonesia, 2026)
Honesty is a valuable moral value that must be owned by everyone. Researchers are trying to find alternative ways to instill this attitude of honesty. Therefore, this study aims to examine the related literature whether the Living Values Education (LVE) learning model emphasizes character education? Can this LVE model be an alternative Islamic education learning model that can train students' honesty? This study uses a qualitative approach with the method of literature study. Data was collected through document study, then analyzed using content analysis method, then data was presented using description method. The results of this study indicate that the Life Values Education learning model can foster student morale such as the moral values of tolerance, anti-radicalism, responsibility, peace, and respect. Application of the LVE in Islamic Religious Education learning significantly instills and enhances honesty in students. This is evident in the changes student behavior, leading to greater honesty in speech, attitude, and actions. LVE model also encourages active student involvement through value reflection, discussion, and role modeling, making Islamic Religious Education learning more meaningful and character oriented. This is a reference that the LVE model can be used as an alternative to instill an attitude of honesty as well.